CO2/N2-Responsive Nanoparticles for Enhanced Oil Recovery During CO2 Flooding - Lai, Nanjun; Zhu, Qingru; Qiao, Dongyu; Chen, Ke; Wang, Dongdong; Tang, Lei; Chen, Gang (Frontiers in Chemistry, 2020)
High mobility of CO2 relative to crude oil and formation water lead to low sweep efficiency or serious gas channeling in ultra-low permeability reservoirs. The primary objective of this work was to investigate responsive nanoparticles to apply for mobility control to enhanced oil recovery. Responsive nanoparticles were developed based on the 3-aminopropyltrimethoxysilane (KH540) modified nano-silica (SiO2) via Eschweiler-Clark reaction. The prove to concept for responsive nanoparticles was investigated by FT-IR, 1H-NMR, TEM, DLS, CO2/N2 response, wettability, plugging performance and core flooding experiments. Results indicated that responsive nanoparticles exhibited a good response to control nanoparticles dispersity due to electrostatic interaction. Subsequently, responsive nanoparticles shown fascinating plugging capacity gas channeling with a plugging efficiency of 93.3% to control CO2 mobility, and more than 26% of original oil was recovered. Moreover, the proposed responsive nanoparticles could reverse oil-wet surfaces to water-wet state relying on surface adsorption to assist the oil displacement. The results of this work indicated that responsive nanoparticles might have potential application for enhanced oil recovery during CO2 flooding in ultra-low permeability reservoirs.